2020
DOI: 10.3390/molecules26010141
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodechlorination of 4-Chlorophenol on Pd-Fe Catalysts on Mesoporous ZrO2SiO2 Support

Abstract: A mesoporous support based on silica and zirconia (ZS) was used to prepare monometallic 1 wt% Pd/ZS, 10 wt% Fe/ZS, and bimetallic FePd/ZS catalysts. The catalysts were characterized by TPR-H2, XRD, SEM-EDS, TEM, AAS, and DRIFT spectroscopy of adsorbed CO after H2 reduction in situ and tested in hydrodechlorination of environmental pollutant 4-chlorophelol in aqueous solution at 30 °C. The bimetallic catalyst demonstrated an excellent activity, selectivity to phenol and stability in 10 consecutive runs. FePd/ZS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…This may be one of the main reasons for the high activity of the catalyst. The reduction peaks of both catalysts, Pd 4 Fe 1 / N x C@mSiO 2 , were reduced compared to Pd 5 /N x C@mSiO 2 , indicating that the doping of Fe made Pd easier to be reduced, and the reduction peak of Pd 4 Fe 1 /N x C@mSiO 2 was also reduced compared to the reduction temperatures reported in the literature, 30 which indicated that the electrons between Pd and Fe shifted to each other, which made it easier to be reduced, as with the XPS peak splitting results. CO as a reactant for carbonylation, the insertion of CO in the carbonylation reaction is crucial and an important step.…”
Section: Pd 4 Fe 1 /N X C@msio 2 Characterization and Performance Tes...mentioning
confidence: 62%
“…This may be one of the main reasons for the high activity of the catalyst. The reduction peaks of both catalysts, Pd 4 Fe 1 / N x C@mSiO 2 , were reduced compared to Pd 5 /N x C@mSiO 2 , indicating that the doping of Fe made Pd easier to be reduced, and the reduction peak of Pd 4 Fe 1 /N x C@mSiO 2 was also reduced compared to the reduction temperatures reported in the literature, 30 which indicated that the electrons between Pd and Fe shifted to each other, which made it easier to be reduced, as with the XPS peak splitting results. CO as a reactant for carbonylation, the insertion of CO in the carbonylation reaction is crucial and an important step.…”
Section: Pd 4 Fe 1 /N X C@msio 2 Characterization and Performance Tes...mentioning
confidence: 62%
“…5 b) proved the presence of various valence states of metals in the catalyst. The reduction temperature of Co and Fe in the higher valence state is lower compared to the corresponding oxides of Co and Fe, indicating that the Co and Fe in the catalyst form a more stable structure than the oxides, further confirming the formation of the C–O–M bond linkage [ 12 , [53] , [54] , [55] , [56] ]. In addition, the reduction peaks of Zn 2+ →Zn 0 shifted to the high-temperature region after the introduction of Fe and Co, indicating that Zn was protected, more difficult to reduce, and became the substrate for the catalyst to make the catalyst structure more stable, while Co and Fe were the main active sites of the catalyst.…”
Section: Resultsmentioning
confidence: 98%
“…Supporting information contains a literature survey on the hydrogen-transfer hydrodechlorination of 4-chlorophenol in liquid phase with additional references, [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] XRD patterns of γ-Al 2 O 3 support and its prepared catalysts, XPS spectra of the synthesized catalysts, HAADF-STEM images of fresh and spent Pt/γ-Al…”
Section: Supporting Information Summarymentioning
confidence: 99%
“…Supporting information contains a literature survey on the hydrogen‐transfer hydrodechlorination of 4‐chlorophenol in liquid phase with additional references, [53–72] XRD patterns of γ‐Al 2 O 3 support and its prepared catalysts, XPS spectra of the synthesized catalysts, HAADF‐STEM images of fresh and spent Pt/γ‐Al 2 O 3 catalyst, SEM images and EDX‐spectra of Pt/γ‐Al 2 O 3 , Rh/γ‐Al 2 O 3 , Ru/γ‐Al 2 O 3 and Pt/γ‐Al 2 O 3 catalysts, GC chromatograms of starting materials, products and representative examples of some experiments.…”
Section: Supporting Information Summarymentioning
confidence: 99%